The turnovers analysis to the women's national league basketball games - Fylaktakidou, A.; Tsamourtzis, E.; Zaggelidis, G. (Sport Science Review, 2011)
The purpose of this study was to describe and analyze the turnovers efficacy to the result of a basketball game. For the purpose of this study forty-three (n=43) women A1 National league basketball games were videotaped and video-analyzed. Statistical analysis of this data included the presentation of frequencies in a double table and the application of x2. The results showed that a) 19,1% of the possessions stop after a turnover, b) the most common turnover to the women basketball is the passing errors (40,2%). Travelling (23,6%) and fault ball handling (23,9%) follow, c) most of the turnovers happen during the set play, d) most of the fault passes take place from the area around the three point line to the opposite base line, most of the traveling and the fault ball handling to the area around the basket and inside the three point line, e) the ability to defeat the zone defense is of a real importance because the women basketball teams use to play this defense and most of the turnovers seems to happen under these circumstances (winners 16,5% - losers 22,2%).